How to walk to schoo [ blueprint for a neighborhood school renaissance - Edelberg, Jacqueline , 1967-; Kurland, Susan , 1945- (Rowman & Littlefield Education, 2009)
Here is the story of motivated neighborhood parents organizing an entire community to help transform a challenged urban school into one of Chicago's best. Author Jacqueline Edelberg, one of the neighborhood moms, provide an accessible and honest blueprint for reclaiming the public schools our children deserve.--[book jacket]